2012
DOI: 10.1007/978-3-642-35386-4_36
|View full text |Cite
|
Sign up to set email alerts
|

Dark Retweets: Investigating Non-conventional Retweeting Patterns

Abstract: Abstract. Retweets are an important mechanism for recognising propagation of information on the Twitter social media platform. However, many retweets do not use the official retweet mechanism, or even community established conventions, and these "dark retweets" are not accounted for in many existing analysis. In this paper, a comprehensive matrix of tweet propagation is presented to show the different nuances of retweeting, based on seven characteristics: whether it is proprietary, the mechanism used, whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Survey respondents stated that they tended to retweet content they found credible, trustworthy, interesting, agreeable, or entertaining from accounts they believed were credible and trustworthy (Metaxas et al 2015). However, other work has suggested that retweets may not always indicate support (Macskassy and Michelson 2011), particularly when they are expressed via unofficial means (e.g., via adding the text "RT" to beginning of the tweet (Azman, Millard, and Weal 2012)). Even via the official mechanism, at least in highly polarized domains like sports and politics, betweengroup retweet rates can actually exceed within-group rates.…”
Section: Measurement Of Politically-relevant Contentmentioning
confidence: 99%
“…Survey respondents stated that they tended to retweet content they found credible, trustworthy, interesting, agreeable, or entertaining from accounts they believed were credible and trustworthy (Metaxas et al 2015). However, other work has suggested that retweets may not always indicate support (Macskassy and Michelson 2011), particularly when they are expressed via unofficial means (e.g., via adding the text "RT" to beginning of the tweet (Azman, Millard, and Weal 2012)). Even via the official mechanism, at least in highly polarized domains like sports and politics, betweengroup retweet rates can actually exceed within-group rates.…”
Section: Measurement Of Politically-relevant Contentmentioning
confidence: 99%
“…Considering the 40 user case, node 40 and 1 both send a message at the same time with equal uniform probability to a node i, and the firing of a sequence of messages is equally attributed to both nodes. It may be seen a fault of the model to not accurately attribute the responsibility for the accumulated effort in the numerator for this activity, but this encapsulates the feature that nodes can mimic the images of higher ranked nodes with techniques such as 'dark' tweeting (removing credit of origin and repeating Azman et al (2012)). Another process is that nodes do not separate repeater and origin credit (sharing/retweeting) which is possible for those that simply copy valuable content.…”
Section: Resultsmentioning
confidence: 99%
“…This study highlighted the importance of network on the spread and adoption of various information dissemination conventions, and also noted the importance of design changes in Twitter's interactional features in this process. A detailed analysis of various non-conventional ways of retweeting and their impact is discussed in [1]. Prior to the introduction of quote RTs, users could not comment on a tweet while retweeting.…”
Section: Related Workmentioning
confidence: 99%
“…Giving weight to the view held by cyber-pessimists, in recent years there has been a rise of trolls and abuse in social media, particularly in partisan political discourse 1 . Especially the comment sections on political news websites often serve as example of "less than ideal" political discourse.…”
Section: Introductionmentioning
confidence: 99%